Petroleum: The Petroleum-Spirit (conveyance by Road) Regulations, 1957 - Her Majesty's Stationary Office (Her Majesty's Stationary Office, 1957)
These Regulations consolidate with amendments the regulations specified in Regulation 29. The principal amendment of substance is tbe inclusion of Regulation 16, tbe provisions of which are new and relate to the precautions to be taken in connection with tbe delivery of petro1eum-spirit from a tank wagon or tank trailer into a storage tank
ERAF: A6 SI 1957:191
Keywords: Petroleum; Statutory Instruments; Spirit; Regulations